1994
DOI: 10.1002/mus.880170610
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index and the diagnosis of carpal tunnel syndrome

Abstract: Increased weight and, more recently, body mass index (BMI), have been suggested as risk factors for carpal tunnel syndrome (CTS). In an effort to determine the relative risk (RR) of obesity in the development of CTS, 949 patients who had an evaluation of the right upper extremity that included motor and sensory conduction studies of the median and ulnar nerves were reviewed. Of these patients, 261 were diagnosed with a median mononeuropathy at the wrist. Those individuals who were classified as obese (BMI > 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
137
1
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(161 citation statements)
references
References 10 publications
16
137
1
7
Order By: Relevance
“…For example, with symptoms and MM-0.5 as criteria, between 2% and 7% of the workers in our study had CTS in the dominant hand. In comparison, a 27% prevalence of CTS was found in a study conducted among a large clinical population (33). In addition, thenar atrophy, often reported in clinical populations, was rarely observed in this group.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, with symptoms and MM-0.5 as criteria, between 2% and 7% of the workers in our study had CTS in the dominant hand. In comparison, a 27% prevalence of CTS was found in a study conducted among a large clinical population (33). In addition, thenar atrophy, often reported in clinical populations, was rarely observed in this group.…”
Section: Discussionmentioning
confidence: 67%
“…The clinical tools employed in this study, including hand diagrams, physical examination procedures, and sensory nerve conduction tests performed by experienced clinicians, are widely used clinically and in epidemiologic studies of CTS, and they are generally recognized as pertinent to defining the clinical syndrome. Electrodiagnostic findings can also be influenced by other factors, such as obesity, age, height, finger circumference and wrist ratio (33,34). However, the use of the median minus ulnar peak latency difference, as employed in this study, has been shown to be the least sensitive measure to such covariates (35).…”
Section: Discussionmentioning
confidence: 83%
“…Idiopathic CTS is more common in females, middle-aged patients and those with an increased body mass index (BMI) [2]. Diseases such as diabetes, rheumatoid arthritis, and hypothyroidism, also carry an increased risk of developing CTS [3].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of patients with CTS have revealed a consistent relationship between being overweight and 1) having a mononeuropathy of the median nerve, 2) being diagnosed with CTS, and 3) undergoing surgical intervention for CTS (Stallings, Kasdan, Soergel & Corwin, 1997;Nordstrom, Vierkant, DeStefano, & Layde, 1997;Tanaka et al, 1997;Werner & Franzblau, 1994). Workers with a body mass index (BMI; kg/m 2 ) greater than 25 have been shown to be four times as likely to present with a median mononeuropathy than coworkers with a BMI less than 25 .…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%